2021
DOI: 10.3390/ijms22063176
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Primary Cilia during Peripheral Nervous System Formation

Abstract: The primary cilium plays a pivotal role during the embryonic development of vertebrates. It acts as a somatic signaling hub for specific pathways, such as Sonic Hedgehog signaling. In humans, mutations in genes that cause dysregulation of ciliogenesis or ciliary function lead to severe developmental disorders called ciliopathies. Beyond its role in early morphogenesis, growing evidence points towards an essential function of the primary cilium in neural circuit formation in the central nervous system. However,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…These data were in line with previous reports in the chicken spinal cord with newly differentiated interneurons in vivo and cultured commissural neurons, respectively (Toro-Tapia and Das, 2020; Yusifov et al, 2021). Moreover, the ciliation of dI1 neurons in the chicken was confirmed by immunostaining for adenylate cyclase III (ACIII), a known neuronal primary cilia marker (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These data were in line with previous reports in the chicken spinal cord with newly differentiated interneurons in vivo and cultured commissural neurons, respectively (Toro-Tapia and Das, 2020; Yusifov et al, 2021). Moreover, the ciliation of dI1 neurons in the chicken was confirmed by immunostaining for adenylate cyclase III (ACIII), a known neuronal primary cilia marker (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The most dorsal part of the spinal cord, containing mostly dI1 commissural neurons, was cut from 6-7 open-book preparations of wild-type HH25-26 embryos in cold sterile PBS as previously described (Yusifov et al, 2021). Cells were dissociated with 0.25% Trypsin in PBS (Invitrogen, cat# 15090-046), containing 0.2% DNase (Roche, cat# 101 041 590 01), at 37°C for 20 min followed by a sequence of trituration in different pre-warmed media (37°C; MEM (Gibco) with 5% FCS (Gibco), MEM only, and finally in commissural neuron medium) with fire-polished Pasteur pipettes and centrifugation at 1000 rpm for 5 min at room temperature in-between.…”
Section: Commissural Neuron Cultures In Microfluidic Chambersmentioning
confidence: 99%
“…Indeed, it has long been observed that primary cilia are present not only in mature neurons but also in several kinds of cells, including neural crest cells, neural progenitor cells, and glial cells ( Etchevers et al, 2019 ; Park S.M. et al, 2019 ; Yusifov et al, 2021 ). Moreover, primary cilia are organelles that undergo assembly and disassembly depending on the type of cell or developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The primary cilium has an important role in the CNS, but is also pivotal to the formation of the peripheral nervous system (PNS) in vivo. [6] However, PNS abnormalities in patients with JS have yet to be reported.…”
Section: Introductionmentioning
confidence: 99%